Don’t They Deserve Love? Analysing The Enduring Impact of Victorian-Era Laws on The Rights of LGBT Individuals in Sri Lanka - Thamasi, K.; Piyumi, L.; Chathura, H. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and Surana International Attorneys India, 2025)
Love is a basic need. Every individual throughout their lives needs to feel connected to someone of something. The need of love begins with the birth and continuous throughout the existence of an individual. During the adulthood, this need is centred around the concept of marriage and finding a family. Being homosexual is not an exception to this. Yet the Victorian definition of marriage is limited to union between a man and women for a lifetime. With the influence of British colonialism, domestic law has continued to criminalize homosexual relationships and restrict marriages to heterosexual couples in Sri Lanka. When the right to choose who to love and to whom to get married is an offence with criminal penalties, such laws seriously infringe certain human rights including right to equality and right to dignity. Even though, homosexuality has been a topic in the existing literature, there is a gap in the doctrinal research on the legal restrictions of homosexual relationships. The objective of this qualitative research was to analyse the impact of outdated Victorian concepts on relationships embodied in domestic law in realizing certain human rights of homosexual individuals. This research was based on normative judicial research methodology with reference to available secondary data. Findings of this research reveals that, the impact of gender and sex regulatory laws introduced by the British to the Sri Lankan Legal system has created platform for the continuous discrimination against homosexual individuals up until today. Despite the international human rights obligations, Sri Lanka is still upholding the colonial discriminatory laws which infringes rights of the homosexual individuals. After an in-depth analysis on the existing international and national obligations, the main recommendation is to decriminalize homosexuality in Sri Lanka. Therefore, the section 365 and 365 A of the Penal Code of Sri Lanka must be amended accordingly.
Keywords: Colonialism; Criminalization; Homosexuality; Relationship; Right to family